The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1088/1468-6996/10/1/015006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of platinum–iron catalysts supported on MCM-41 synthesized with rice husk silica and their performance for phenol hydroxylation

Abstract: Mesoporous material RH-MCM-41 was synthesized with rice husk silica by a hydrothermal method. It was used as a support for bimetallic platinum−iron catalysts Pt-Fe/RH-MCM-41 for phenol hydroxylation. The catalysts were prepared by co-impregnation with Pt and Fe at amounts of 0.5 and 5.0 wt.%, respectively. The RH-MCM-41 structure in the catalysts was studied with x-ray diffraction, and their surface areas were determined by nitrogen adsorption. The oxidation number of Fe supported on RH-MCM-41 was +3, as deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…The product selectivity in the reaction catalyzed by Fe/MCM-41 could be changed by changing the reaction conditions and support acidity [6,7]. Chumee et al [9] reported that catalysts supported on RH-MCM-41 provided a faster conversion than that supported on rice husk silica [9]. The mesoporous structure of MCM-41 may facilitate the diffusion of the reactants and products.…”
Section: Introductionmentioning
confidence: 99%
“…The product selectivity in the reaction catalyzed by Fe/MCM-41 could be changed by changing the reaction conditions and support acidity [6,7]. Chumee et al [9] reported that catalysts supported on RH-MCM-41 provided a faster conversion than that supported on rice husk silica [9]. The mesoporous structure of MCM-41 may facilitate the diffusion of the reactants and products.…”
Section: Introductionmentioning
confidence: 99%
“…Rice husk silica was extracted with HCl acid. The resulting silica product showed the amorphous silica's purity as greater than 98 wt% (Chumee et al 2009). Sodium silicate prepared from rice husk silica can be used as a source of silica to synthesize mesoporous materials such as MCM-41 (Grisdanurak et al 2003;Chiarakorn et al 2007;Chumee et al 2009).…”
Section: Introductionmentioning
confidence: 96%
“…The resulting silica product showed the amorphous silica's purity as greater than 98 wt% (Chumee et al 2009). Sodium silicate prepared from rice husk silica can be used as a source of silica to synthesize mesoporous materials such as MCM-41 (Grisdanurak et al 2003;Chiarakorn et al 2007;Chumee et al 2009). The MCM-41, with one-dimensional hexagonal mesopores (2-50 nm) and high surface area ([750 m 2 g -1 ), has attracted considerable interest for various applications, especially for gas adsorption (Grisdanurak et al 2003;Chiarakorn et al 2007).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A number of possible uses for RHA include absorbents for oils and chemicals, soil ameliorants, a source of silicon, insulation powder in steel mills, as repellents in the form of "vinegar-tar" release agent in the ceramics industry, as an insulation material. More specialized applications include the use of this material as a catalyst support (Chumee et al, 2009). The main aim of this study was to determine various physical properties of RHA and important mechanical properties of concrete containing different amount of RHA.…”
Section: Introductionmentioning
confidence: 99%